SYSTEMATIC LITERATURE REVIEW BLOCKCHAIN UNTUK TATA KELOLA E-GOVERNMENT: MEKANISME TRANSPARANSI, AKUNTABILITAS, AUDITABILITY, PRIVASI, DAN ADOPSI DI SEKTOR PUBLIK - Ucu Nugraha; Sri Titi Handayani; Hernalom Sitorus; Irawan Afrianto; Estiko Rijanto; Irfan Dwiguna Sumitra (LPPM Universitas Abdurrab, 2026)
Digital transformation in government has intensified the need for public service governance that is transparent, accountable, auditable, and privacy-compliant. Blockchain and smart contracts can strengthen governance through immutability, traceability, and rule automation, yet they introduce transparency–privacy trade-offs, cross-agency interoperability constraints, and socio-technical adoption barriers. This study conducts a Systematic Literature Review (SLR) to synthesize governance mechanisms—transparency, accountability, auditability, and privacy—together with technical implementation patterns and adoption factors in e-government. We searched Scopus using a TITLE-ABS-KEY query with Open Access and English-language filters; PRISMA screening yielded 118 included studies. Results map dominant use cases (general e-government services, digital identity/credentials, e-voting, and cross-agency data sharing) and show that evidence maturity is still prototype-heavy (63/118). A critical finding is pervasive under-reporting of key technical descriptors that weakens synthesis and comparability: 72/118 studies do not specify the blockchain type and 85/118 do not report the platform; 109/118 also omit on-chain/off-chain design. The SLR contributes an evidence map and governance mechanism taxonomy, and can be operationalized as an assessment checklist for governments/consultants to question governance mechanisms, planned outcome metrics, and transparency–privacy trade-offs prior to deployment.